Gendering Colour: Identity, Femininity and Marriage in Kerala - Philips, Amali (Anthropologica, 2022)
This paper uses ethnographic material on the Christian middle class in the South Indian state of Kerala, to explore the significance of skin colour as symbolic capital for marriage and dowry negotiations. Within the social contours of caste, community and marriage circles, fair-skin colour and other female embellishments operate as ’’boundary markers" to accentuate marital, caste and class positions and feminine gender identity. South Indian and South Asian perceptions of "fair skin colour" as a defining feature of female beauty ideals and feminine gender identity incorporate other related qualities such as health and moral conduct. Skin colour, along with dowry negotiations, serves to disempower women both symbolically and materially in the matter of their own marriages.